Theological English: An Advanced ESL Text for Students of Theology - Hibbs, Pierce T.; Reiley, Megan (P & R Publishing; New Jersey, 2018)
A finalist for the 2019 Christian Book Awards, Theological English is an advanced ESL textbook that helps non-native English speakers gain access to the rich theology of the Reformed tradition. With 30 lessons covering the major genres of theology (apologetics, biblical studies, church history, systematic theology, and practical theology), Theological English invites students to engage with English while exploring answers to relevant biblical and theological questions. In answering such questions, students encounter passages from theologians in the Reformed tradition, both historical and modern, and build their skills in reading, listening, speaking, and writing English. Students then practice these skills by completing various relevant tasks throughout the textbook. These tasks help students move from learning theological English to using theological English. If you want to study theology in English at an advanced level, this is the text for you.